Pelatihan Penyusunan Laporan Keuangan Berbasis SAK EP Bagi Pelaku UMKM UD. Kusuma Bali Mandiri Cabang Karangasem - Adisti Krisna; Ni Putu Kusuma Widanti; Ni Wayan Septia Wini; Ida Ayu Agung Paramitaswari; Ni Kadek Pajar Kusumawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas KH. A. Wahab Hasbullah, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in the national economy, including in Karangasem Regency, Bali. One active business player in this region is UD. Kusuma Bali Mandiri, Karangasem Branch, which is facing challenges in preparing financial reports in accordance with the Financial Accounting Standards for Entities Without Public Accountability (SAK EP). The manual recording of transactions results in low-quality financial information, hampering decision-making, access to financing, and business performance evaluation. In response, a team of lecturers from the Denpasar Academy of Finance and Banking (AKABA) conducted community service activities in the form of training on preparing financial reports based on SAK EP. This activity aims to improve the understanding and skills of MSMEs in preparing accurate, systematic financial reports in accordance with accounting standards. The implementation method included lectures, practical tutorials using spreadsheet software, and interactive discussion sessions oriented to partner needs. The results of the activity showed a significant increase in participants' ability to understand basic accounting concepts and the application of SAK EP in financial recording. Through this training, it is hoped that MSMEs will be able to implement more professional and transparent financial governance and support business sustainability. This program also serves as a tangible form of higher education's contribution to community empowerment and improving financial literacy in the region.